Implementation of Balanced Nutrition Guidelines and Their Association with Children’s Nutritional Status in Private and Public Elementary Schools of Pekalongan Regency - Mikhael Andya Sekar Putri; Ali Khomsan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Double malnutrition has become a major nutritional concern among elementary school children, potentially impairing growth, development, and academic performance. This study aims to analyze the implementation of balanced nutrition and nutritional status in school-age children. Methods: A cross-sectional design was applied from November – December 2024 at SDIT Plus Mutiara Umat (private school) and SDN 1 Wiroditan (public school), Pekalongan Regency, Central Java, Indonesia. A total of 140 students (70 from each school) were selected through simple random sampling. Data collection included self-administered questionnaires, 24-hour food recall, Individual Dietary Diversity Score (IDDS), and anthropometric measurements. Statistical analyses were performed using the independent t-test for normally distributed data and the Mann–Whitney test for non-normal distributions. Results: Most parents in private school have completed college education (58.6%) while in public school only completed high school education (48.6%). Most subjects in private school had lower pocket money than in public schoolObesity prevalence was higher in private schools (15.7%), while underweight was more frequent in public schools (8.6%). Most respondents exhibited moderate nutritional knowledge (private: 68.6%; public: 77.1%) and negative nutritional attitudes (private: 88.6%; public: 94.3%). Moderate dietary diversity was observed in both groups. Public school students showed significantly higher energy, fat, and carbohydrate intakes (p < 0.05). Significant differences were also found in pocket money, maternal education, nutritional status, and attitude (p < 0.05). Conclusion: This study contributes provides information to the community regarding balanced nutrition and the nutritional status of school-aged children. The findings of this research can serve as a reference for schools in promoting the implementation of balanced nutrition and for government may be used as a source of literature in development of programs aimed at achieving normal nutritional status among children.